Antibacterial Activity of Phenol Gracillaria verrucosa Extract on Aeromonas Salmonicida Bacteria in vitro - Moh. Awaludin Adam; Hardoko Hardoko; Maftcuh Maftcuh (Natural B, Journal of Health and Environmental Sciences, 2013)
The aim of research were to investigeste the effect of antibacterial activity of phenolic extracts Gracillaria verrucosa on the growth of bacteria Aeromonas salmonicida and the number of doses and optimal time extract. The method used was an experiment with a completely randomized design (CRD). The concentration of the extract used were 1 ppt, 1.5 ppt and 2 ppt. Each treatment was done 3 replications. Based on the test results of ANOVA (Analysis of Variance) showed that the average value of the inhibition of post Gracilaria verrucosa phenol extract was significantly different (p <0.05). LSD (Least Significant Difference) showed that Gracilaria verrucosa phenol extract at a dose of 1.5 ppt has the highest average value of the inhibition by 15 mm, followed by a dose of 1 ppt and 2 ppt with a mean of respectively 10 mm and 11 mm.